Effectiveness of Mirror Therapy on Phantom Limb Pain in patients with Below Knee Amputation - Dhongade, Isha; Kanase, Suraj B. (Journal of Neonatal Surgery, 2025)
Background:When a limb is severed or its sensory roots are destroyed, it is typical to experiece the phenomena of a phantom limb.1 PLP frequently affects patient’s quality of life and increases the limitations caused by amputation, potentially compromising social or professional reintegration. Mirror therapy has not gained widespread use for unilateral below-knee amputation, despite early interest in treating phantom limb pain. Aim of this research is to see the effectiveness of mirror therapy on phantom limb pain in patients with below knee amputation. Methods: 49 individuals who had undergone a unilateral below-knee amputation were split into two groups at random: Group A underwent mirror therapy in addition to conventional therapy, while Group B only received conventional therapy. For three weeks, both groups attended intervention sessions five days a week. The SF36 health survey, the visual analogue scale (VAS), and the brief pain inventory (BPI) were among the outcome measures. Scores before and after the intervention were noted and compared between groups. Result:In comparison to Group B, Group A showed larger numerical decreases in pain intensity (VAS); nevertheless, this difference was not statistically significant (P > 0.05).Significant gains in Group A's SF36 Physical and Mental Health ratings were noted (P < 0.05), suggesting that mirror therapy improved quality of lifeGroup-to group variations in BPI scores were similar. Conclusion: These findings support the integration of mirror therapy into conventional rehabilitation programs for amputees, particularly to improve quality of life and functional recovery. Further studies with larger samples and long-term follow-up are warranted to confirm these outcomes